Improvement in renal function after switching from entecavir to tenofovir alafenamide in chronic hepatitis B patients with low estimated glomerular filtration rates - Liang Wang; Shipeng Ma; Lajpat Rai Malhi; Xiaoping Wu; Liping Liu; Xin Wan; Yuliang Zhang; Xiaopeng Li; Shanfei Ge (Annals of Hepatology, 2025)
Introduction and Objectives: Tenofovir alafenamide (TAF) and entecavir (ETV) are both considered renal-friendly nucleoside/nucleotide analogs (NAs). However, the difference between ETV and TAF in terms of renal function remains unclear. This study aims to compare the renal safety profiles of two antiviral medications directly and evaluate the impact of switching from ETV to TAF treatment on renal function in chronic hepatitis B (CHB) patients with low estimated glomerular filtration rates (eGFR). Patients and Methods: A total of 179 CHB patients who received TAF (n = 84) or ETV (n = 95) between 2019 and 2023 were included in the study. Changes in eGFR levels between two treatment groups from baseline to 72 weeks were compared to measure the influence of these NAs on renal function. Results: At baseline, 84 patients were included in each treatment group after a 1:1 propensity score matching process. At week 48, a notable different changes in eGFR were observed between the two groups. Gender, baseline eGFR, and medication (TAF/ETV) were significantly correlated with eGFR abnormalities. Furthermore, eGFR abnormalities at week 48 led to the transition of 6 patients in the ETV group to TAF. eGFR significantly increased (83.60 ± 5.45 vs. 93.39 ± 9.88 mL/min/1.73 m2; p = 0.031) and serum creatinine significantly decreased (81.47 ± 11.36 vs. 74.9 ± 10.67 μmol/L; p = 0.046) from week 48 to 60. At week 48, the incidence of low-level viremia (LLV) was 19.0 % in the ETV group and 16.7 % in the TAF group, respectively (p > 0.05). Pairwise comparisons revealed no significant difference in the percentage of LLV between the ETV continued group and the TAF continued group at week 48, 60, and 72. Additionally, there was also no significant difference in the proportion of LLV between the ETV + TAF combination group and the TAF + ETV combination group at week 48, 60, and 72. Conclusions: There was a substantial difference in eGFR between ETV and TAF treatments at week 48. Gender, baseline eGFR, and medication (TAF/ETV) were all remarkably positive indicators of eGFR abnormalities. In patients receiving ETV, an early switch to TAF may result in the reversal of early-stage renal damage.